THE DEVELOPMENT OF LEARNING MEDIA OF REALISTIC MATHEMATICS LEARNING BASED MACROMEDIA FLASH ON RECTANGLE AND SQUARE MATERIALS FOR JUNIR HIGH SCHOOL STUDENTS - Sholahudin Al’Ayubi; Haning Hasbiyati (FKIP Universitas Islam Jember, 2015)
Mathematics is a basic discipline. Either on the aspect of logical reasoning or its applications, it is very useful in daily lives and in the effort of progression of mastering knowledge and science as well. The current conditions of mathematics learning in Indonesia are highly required serious attention that caused by a lot of problems raised on math learning (e.g., Math curriculum, learning model, teachers’ qualification, and students’ low motivation). In accordance with the previous illustrations, this research is aimed at (1) investigating the development of realistic Math learning, macromedia flash media-based, on the subject of rectangle and square for seventh grade students of junior high school, and (2) developing and/or producing media-based math learning macromedia flash on the subject of rectangle and square for seventh grade students of junior high school. In this study the researchers use research and development as research design focused on developing media-based realistic math learning using macromedia flash. The products of this study to be developed are lesson plan (RPP), modules for teachers and students, students’ worksheets, and the students’ achievement test/evaluation. After conducting experts’ validation and try out, this macromedia flash media-based only need a minor revision. It, therefore, was categorized as good.Keywords: Realistic Mathematics, macromedia flash.